Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/appy.12371
|View full text |Cite
|
Sign up to set email alerts
|

Preventing suicide, promoting resilience: Is this achievable from a global perspective?

Abstract: Suicide continues to be a major health concern globally despite many initiatives to identify risk factors and methods for suicide prevention. We have carried out a detailed narrative review of the literature from 2016 to 2019 using the headings of Personal resilience (P1), People (P2), Places (P3), Prevention (P4), Promoting collaboration (P5), and Promoting research (P6) in order to support an integrated approach to suicide prevention and the promotion of personal and population resilience. We have made 10 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 67 publications
0
20
5
Order By: Relevance
“…According to the distress/protection model of QOL ( Voruganti et al., 1998 ), QOL is determined by the interaction between protective (e.g., good social support and high socioeconomic status) and distressing factors (e.g., physical diseases and mental disorders). Considering the negative impact of depression on the quality of clinical practice and its symptom profile including hopelessness, helplessness, insomnia, cognitive impairment, and somatic complaints ( Ivbijaro et al., 2019 ; Singleton, 2001 ), it is reasonable to assume that depressed nurses are far more likely to have lower QOL than nurses without depression. In this study depressed nurses reported lower QOL than those without, which echoed previous findings ( Malhi and Mann, 2018 ; Sjoberg et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the distress/protection model of QOL ( Voruganti et al., 1998 ), QOL is determined by the interaction between protective (e.g., good social support and high socioeconomic status) and distressing factors (e.g., physical diseases and mental disorders). Considering the negative impact of depression on the quality of clinical practice and its symptom profile including hopelessness, helplessness, insomnia, cognitive impairment, and somatic complaints ( Ivbijaro et al., 2019 ; Singleton, 2001 ), it is reasonable to assume that depressed nurses are far more likely to have lower QOL than nurses without depression. In this study depressed nurses reported lower QOL than those without, which echoed previous findings ( Malhi and Mann, 2018 ; Sjoberg et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model postulated that an individual's satisfaction with QOL decreases if the distress factors outweigh protective factors, and vice versa (15). It has been consistently found that clinicians with emotional disturbances report lower QOL than those without (3,16,17). Clinicians exposed to violence are likely to have lower QOL in both physical and mental domains (18).…”
Section: Introductionmentioning
confidence: 99%
“…Family environment plays an important role in shaping the behaviors of children and adolescents. According to Attachment Theory, the parent-child relationship is the primary relationship that a child has and the health of the relationship influences child's social and emotional development (Bowlby, 1988;Brumariu, 2015;Ivbijaro et al, 2019). Parents are the primary agents of children's socialization (Collins et al, 2000) and key contributors to youth health and development (Sze, Ba & Dai, 2020;Whitlock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%